Seasonal dynamics of the phage-bacterium linkage and associated antibiotic resistome in airborne PM2.5 of urban areas - Tangtian He; Jiawen Xie; Ling Jin; Jue Zhao; Xiaohua Zhang; Hang Liu; Xiang Dong Li (Environment International, 2024)
Inhalable microorganisms in airborne fine particulate matter (PM2.5), including bacteria and phages, are major carriers of antibiotic resistance genes (ARGs) with strong ecological linkages and potential health implications for urban populations. A full-spectrum study on ARG carriers and phage-bacterium linkages will shed light on the environmental processes of antibiotic resistance from airborne dissemination to the human lung microbiome. Our metagenomic study reveals the seasonal dynamics of phage communities in PM2.5, their impacts on clinically important ARGs, and potential implications for the human respiratory microbiome in selected cities of China. Gene-sharing network comparisons show that air harbours a distinct phage community connected to human- and water-associated viromes, with 57 % of the predicted hosts being potential bacterial pathogens. The ARGs of common antibiotics, e.g., peptide and tetracycline, dominate both the antibiotic resistome associated with bacteria and phages in PM2.5. Over 60 % of the predicted hosts of vARG-carrying phages are potential bacterial pathogens, and about 67 % of these hosts have not been discovered as direct carriers of the same ARGs. The profiles of ARG-carrying phages are distinct among urban sites, but show a significant enrichment in abundance, diversity, temperate lifestyle, and matches of CRISPR (short for ‘clustered regularly interspaced short palindromic repeats’) to identified bacterial genomes in winter and spring. Moreover, phages putatively carry 52 % of the total mobile genetic element (MGE)-ARG pairs with a unique ‘flu season’ pattern in urban areas. This study highlights the role that phages play in the airborne dissemination of ARGs and their delivery of ARGs to specific opportunistic pathogens in human lungs, independent of other pathways of horizontal gene transfer. Natural and anthropogenic stressors, particularly wind speed, UV index, and level of ozone, potentially explained over 80 % of the seasonal dynamics of phage-bacterial pathogen linkages on antibiotic resistance. Therefore, understanding the phage-host linkages in airborne PM2.5, the full-spectrum of antibiotic resistomes, and the potential human pathogens involved, will be of benefit to protect human health in urban areas.